Reconfiguring the Audience Commodity: The Institutionalization of Social TV Analytics as Market Information Regime. (March 2016) - Kosterich, Allie; Napoli, Philip M.
Changes in the ways that audiences use television, and the ways in which such usage can be measured, raise the possibility of a transformation of the audience commodity, and the currency that fuels the audience marketplace. Specifically, it appears at this point that social media analytics are beginning to play a role in how television program success is measured, and in how advertising dollars are allocated across programs. Essentially, then, the emergence of social TV analytics represents the possibility of a new market information regime taking hold in the audience marketplace. Working from an institutional theoretical framework, this article uses trade materials as a window into industry dynamics and discourses in an effort to provide an account of the recent emergence and usage of social TV analytics in the U.S. television industry and thus explore the process of institutionalization of a new market information regime.